Appearance of cholinergic myenteric neurons during enteric nervous system development: comparison of different ChAT fluorescent mouse reporter lines. Issue 6 (8th April 2014) - Erickson, C. S.; Lee, S. J.; Barlow‐Anacker, A. J.; Druckenbrod, N. R.; Epstein, M. L.; Gosain, A.
Abstract Background Cholinergic neurons have been identified with the acetylcholine synthetic enzyme choline acetyltransferase (ChAT). However, ChAT is difficult to localize in newly differentiated peripheral neurons making the study of cholinergic neuronal development problematic. Consequently, researchers have used mouse reporter lines to indicate the presence of ChAT. Methods Our objective was to determine which ChAT reporter line was the most sensitive indicator of ChAT expression. We utilized two different fluorescent ChAT reporter lines (ChAT‐GFP and ChAT‐Cre;R26R:floxSTOP:tdTomato) together with immunolocalization of ChAT protein (ChAT‐IR) to characterize the spatial and temporal expression of ChAT in myenteric neurons throughout enteric nervous system (ENS) development. Key Results ChAT‐IR cells were first seen in the intestine at E10.5, even within the migration wavefront of neural precursors. Myenteric neurons within the distal small intestine (dSI) and proximal colon were first labeled by ChAT‐IR, then ChAT‐GFP, and finally ChAT‐Cre tdTomato. The percentage of ChAT‐IR neurons is equivalent to adult levels in the dSI by E13.5 and proximal colon by P0. After these stages, the percentages remained relatively constant throughout development despite dramatic changes in neuronal density. Conclusions & Inferences These observations indicate that neurotransmitter expression occurs early and there is only a brief gap between neurogenesis and neurotransmitter expression. Our finding that the proportion of ChAT myenteric neurons reached adult levels during embryonic development suggests that the fate of cholinergic neurons is tightly regulated and that their differentiation might influence further neuronal development. ChAT‐GFP is a more accurate indicator of early ENS cholinergic neuronal differentiation than the ChAT‐Cre;R26R:floxSTOP:tdTomato reporter mouse.